Serum INHB levels and ACE gene I/D polymorphism with increased risk for unexplained infertility. (26th March 2021) - Turan, T; Pekel, A; Duvan, Z C İ; Gönenç, A
Abstract: Angiotensin converting enzyme (ACE) has a significant role in the angiogenesis of ovarian endothelium and the resumption of meiosis and folicular growth. However, there is no any study concerning ACE polymorphism and unexplained infertility (UI). The main aim of this study is that both identify ACE polymorphism and measure the serum ACE, anti-Mullerian hormone (AMH) and inhibin-B (INHB) levels in UI patients and controls in Turkish population. Forty-seven UI patients and 41 controls were involved in this study. To determine the ACE polymorphisms, DNA isolation and PCR were performed. Then, serum ACE, AMH and INHB levels were measured spectrophotometrically. Patients with UI had significantly higher serum INHB levels compared with controls ( P  < 0.05). Serum ACE levels were decreased, compared to controls; however, the decrease was not significant. Serum AMH levels did not significantly differ from controls. When the relationship was analysed between ACE insertion/deletion (I/D) polymorphism and infertility risk, and ID genotype was chosen as reference, it was found to be 2.33 times more risk of UI than the women have DD genotype [DD versus ID: odds ratio = 2.33, 95% confidence interval (0.88–6.19); P  = 0.086]. This finding indicates that DD genotype may be high risk for UI. Further studies are warranted to confirm this finding, especially with a larger population. Graphical Abstract: